Lower back pain and associated factors among weavers working in Bahir Dar City, Northwest Ethiopia: A cross-sectional study - Zinabu, Fiseha Sefiwu; Getie, Kefale; Takele, Mihret Dejen; Chanie, Samuel Teferi; Abich, Yohannes; Shibabaw, Yadelew Yimer; Kibret, Alemu Kassaw (Frontiers in Public Health, 2024)
Background Work-related musculoskeletal disorders are widespread among workers of informal small-scale enterprises. Specifically, lower back pain is a prevalent occupational health problem across various industries, including weaving factories. Lower back pain significantly impairs the functioning, performance, and productivity of weavers. However, information on the prevalence and associated factors of low back pain among weavers of Bahir Dar City and nationwide is scarce. Therefore, this study aimed to assess the prevalence and associated factors of lower back pain among weavers working in Bahir Dar City. Method A multicentered institutional-based cross-sectional study was conducted on 403 weavers in Bahir Dar City, Ethiopia, from April to May 2023 using a structured face-to-face interview questionnaire. Samples were proportionally allocated to each institution, and study participants were selected using a simple random sampling technique. Variables with a P-value < 0.25 in the bivariate logistic regression were adopted for the multivariate logistic regression analysis after verifying the model fitness. In the multivariate logistic regression analysis, the adjusted odds ratio (AOR) with a 95% confidence interval (CI) and a P-value < 0.05 were considered to identify the associated factors of lower back pain among weavers. Result The results revealed that the overall annual prevalence of lower back pain was 63.5% (95% CI = 58.8–68.5). Longer working hours [AOR = 2.580 (CI = 1.517–4.384)], lack of back support [AOR = 1.938 (CI = 2.089–3.449)], repetitive movement of the back during weaving [AOR = 5.940 (CI = 2.709–13.02)], awkward posture [AOR = 2.915 (CI = 1.677–5.065), static working posture [AOR = 4.505 (CI = 2.298–8.831)], and job stress [AOR = 3.306 (CI = 1.896–5.765)] were significantly associated with lower back pain among weavers. Conclusions Lower back pain among weavers was found to be highly prevalent. Working longer hours, lack of back support, repetitive movement of the back, awkward posture, static posture, and job stress were significantly associated with lower back among weavers. The study recommends prompt interventions on weavers to ensure that they use sitting support, weave for <8 h per day, change positions every 2 h, reduce job-related stress, and minimize task repetition, thereby enhancing their working conditions and minimizing the occurrence of lower back pain.